Increasing Knowledge About the Impact of Online Games on Health in Sukasenang Village, Tasikmalaya, Indonesia - Hery Fauzi; Fahmi Sidiq (Research Collaboration Community (RCC), 2021)
The purpose of this study was to describe the factors causing playing online games and their negative impact on students in Sukasenang Village, Tanjungjaya District, Tasikmaya Regency. The subject of this research is that it consists of students playing online games, SDN 1 Cigowak village Sukasenang. Data collection techniques in this study using observation, interviews, and documentation. The results of this study indicate that the factors that cause playing online games and their negative impact on students at the internet cafe at SDN 1 Cigowak village Sukasenang are visible and real. This is proven by the factors that cause children to play online games, namely (a) less than optimal communication between children and family members, especially parents; (b) Lack of parental supervision of children; (c) Errors in parenting patterns from parents to children; (d) The boredom or boredom of a child will be a monotonous routine. Online games have negative impacts including social impacts, psychological impacts, and physical impacts.